Coriander as a natural antimicrobial for meat products: A One Health perspective review - A. E. M. A. Morshdy; A. S. El-tahlawy; A. El-S.E. Hafez; W.S. Darwish (Теория и практика переработки мяса, 2024)
The demand for safe, high-quality meat products drives the need for effective antimicrobial solutions to combat bacterial contamination, a significant health and economic concern. Synthetic preservatives face increasing scrutiny, leading to interest in natural alternatives such as coriander (Coriandrum sativum L.). Known for its culinary and medicinal uses, coriander essential oils, particularly linalool and pinene, exhibit strong antimicrobial properties against a wide range of pathogens. This review examines the phytochemical composition and antimicrobial mechanisms of coriander, and its practical applications in meat preservation through a One Health perspective, which addresses the interconnectedness of human, animal, and environmental health. Coriander offers unique benefits such as a milder flavor and cost-effectiveness. Despite challenges, including variability in antimicrobial efficacy and sensory impacts, its safety profile and regulatory status support its use. Future research should optimize extraction methods, explore synergies with other preservatives, and evaluate long-term safety and efficacy. Coriander is a viable natural solution for improving food safety and quality in the meat industry, aligning with One Health objectives by promoting sustainable practices and reducing health risks across the food production continuum.